Um estudo sobre plantadores de árvores e seu cuidado com as árvores em áreas urbanas públicas de Araras, SP, Brasil - Ribeiro, André Lauand (Universidade Federal de São Carlos, 2018)
The planter´s practice in public areas has not been special focus of academic studies in bibliography regarding urban arborization and greening. This dissertation proposes to narrow this academic gap, through a study about the contemporary tree-planter, as well as to discuss the role of man on caring for the local environment; considering two fundamental aspects: the rural origins of these tree planters and the caring aspect as vital to environment preservation and the return of direct contact of man with Nature in urban areas. The works were intitated with a search and initial observations in newspaper articles and visitation to the majority of the public spaces suit to planting in the municipality of Araras, SP, to come to this issue, that this phenomenon has been poorly studied, in face of a considerable number of planters observed in these areas. Later on, in loco visits, 121 areas of 350 were found (of 420 aproximattely in total) in which was observed practice of planting and caring by dwellers and 57 of them were identified as planters. Of these 57, 17 of them were chosen, in 7 areas, having planting and caring activity. In face of this, we opted to interview them, by means of a guide consisting of semi-structured interviews. The results point that all interviewees have ties with countryside/rural. Moreover, that caring for dwellers precedes maintenance. It emphasizes the tree planter´s role in taking care of Nature in the city. It also points to a renovation in the way of thinking about green areas. For example, inventory of tree planters also could be done (not just tree inventories), of those who engage in planting and taking care of them.
A study about tree planters and their care with trees in public urban areas of Araras, SP, Brazil
Keywords: Arborização urbana; Áreas verdes públicas; Mobilização social; Natureza; Plantadores de árvores; Planejamento verde urbano; Green public areas; Green urban planning; Nature; Social mobilization; Tree planters; Urban arborization; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA URBANA